What can we learn from COVID-19?: examining the resilience of primary care teams - Hughes, Ashley M.; Arredondo, Kelley; Lester, Houston F.; Oswald, Frederick L.; Pham, Trang N. D.; Jiang, Cheng; Hysong, Sylvia J. (Frontiers in Psychology, 2023)
Abstract The COVID-19 pandemic continues to place an unprecedented strain on the U.S. healthcare system, and primary care is no exception. Primary care services have shifted toward a team-based approach for delivering care in the last decade. COVID-19 placed extraordinary stress on primary care teams at the forefront of the pandemic response efforts. The current work applies the science of effective teams to examine the impact of COVID-19—a crisis or adverse event—on primary care team resilience. Little empirical research has been done testing the theory of team resilience during an extremely adverse crisis event in an applied team setting. Therefore, we conducted an archival study by using large-scale national data from the Veterans Health Administration to understand the characteristics and performance of 7,736 Patient Aligned Care Teams (PACTs) during COVID-19. Our study found that primary care teams maintained performance in the presence of adversity, indicating possible team resilience. Further, team coordination to positively predict team performance (B=0.53) regardless of the level of adversity a team experiences. These findings in turn attest to the need to preserve team coordination in the presence of adversity. Results carry implications for creating opportunities for teams to learn and adjust to the adverse event to maintain performance and optimize team-member well-being. Teamwork can act as a protective factor against high levels of workload, burnout, and turnover and should be studied further for its role in promoting team resilience.